Issues on data availability, accessibility, currency and its reliability as inputs in the LCC studies in Malaysia - Ayob, Mohd Fairullazi; Abdul Rashid, Khairuddin (2012)
Commentators often pointed out the main focus of the local practitioners and scholars on LCC in the Malaysian construction industry is considerably on the LCC conversion which includes the methodology and models of computing LCC, but very little emphasis is given on the availability, accessibility, currency and reliability of the data as inputs into the process of generating reliable LCC analysis. This paper presents the application of modified Delphi as a fieldwork approach to investigate the current state and practice of LCC in the Malaysian construction industry with specific reference to data inputs of LCC. A three-round modified Delphi process was implemented to obtain consensus of expert opinion regarding the availability, accessibility, currency and reliability of data as inputs into the process of generating reliable LCC analysis. The study reveals there are several data sources that are categorized as current and reliable data degrees for LCC analysis. However, the results show no single data source is categorized as available and accessible data degrees for LCC analysis. The study concludes that the data to be used as inputs for LCC analysis are limited and inaccessible, which have become significant factors that impose constraints to the implementation of LCC practice in the Malaysia construction industry. This paper is prepared as a part of a three-year research programme.